Reflecting the world : a guide to incorporating equity in mathematics teacher education - Felton-Koestler, Mathew D.; Simic-Muller, Ksenija; Menéndez, José María (Emerald Publishing Limited : Information Age Publishing, Inc., 2017)
Reflecting the World: A Guide to Incorporating Equity in Mathematics Teacher Education is a guide for mathematics teacher educators interested in incorporating equity concerns into their teaching. The book draws on the authors' research and experience integrating issues of equity, diversity, and social justice into their work as mathematics teacher educators of preservice and inservice preK-9 teachers. Reflecting the World includes both a framework for integrating issues of equity into mathematics teacher education courses and professional development and example lessons. The lessons are organized by content area and include guidance for using them effectively.Elementary and middle grades pre-service teachers are often uncomfortable with mathematics, uncertain about their ability to teach it, and unsure of how it connects to the real world. For many preservice teachers a focus on the real world--and in particular on issues of equity, diversity, and social justice--is more engaging than their past experiences with mathematics and can help lessen their mathematical anxieties.Reflecting the World will assist teacher educators in designing and teaching mathematics content and methods courses in ways that support future teachers to see the relevance of mathematics to our world and in becoming critical, questioning citizens in an increasingly mathematical world. The book provides a set of tools for helping future teachers connect mathematics to the lives, interests, and political realities of an increasingly diverse student body, and in doing so it provides a meaningful answer to the question, "when will I ever use this?"